Burnt [videorecording (DVD)] - Cooper, Bradley; Miller, Sienna, 1981-; Sy, Omar, 1978- (Anchor Bay Entertainment, 2016)
Chef Adam Jones had it all, and lost it. A rockstar chef of a two-star Michelin restaurant with the bad habits to match, the former enfant terrible of the Paris restaurant scene did everything different every time out and only ever cared about the thrill of creating explosions of taste. To land his own kitchen and that third elusive Michelin star though, he'll need the best of the best on his side, including the beautiful Helene.